Factors Affecting the Incidence of Filariasis in Welamosa Village Ende District East Nusa Tenggara - Irfan Irfan; Norma Tiku Kambuno; Israfil Israfil (Global Medical & Health Communication (GMHC), 2018)
Filariasis is a chronic communicable disease caused by filarial worms, which consists of three species: Wucherria bancrofti, Brugaria malayi, and Brugaria timori. This disease is transmitted through mosquito bites, infects lymph tissue (lymph) and causes swelling of the legs, breasts, arms and genital organs. Welamosa village, Ende district, located in East Nusa Tenggara (NTT) province is reported as one of the highest cases of 40 cases in 2015. This research aims to analyze the influence of social factor of demography and socio-cultural environment factor to elephantiasis incident in Welamosa village, Ende district. The study was conducted in July–September 2016 in Welamosa village and Wolowaru sub-district, Ende district. The type of research was observational analytic with case-control with 49 people as sampling. The research instrument used questionnaire and check list. The data analysis used statistical test of SPSS program with backward regression logistic test. The results showed five variables as risk factors of elephantiasis occurrence, age (OR=42.518), education (OR=38.248), occupation (OR=8.404), outdoor activity at night (OR=5.097) and sex (OR=0.193). In conclusion, social demographic factors (age, gender, occupation, and education) and environmental and social-cultural factors of attitude (outdoor activities at night) are risk factors for filariasis incidence in Welamosa village, Ende district. FAKTOR YANG MEMENGARUHI KEJADIAN PENYAKIT FILARIASIS DI DESA WELAMOSA KABUPATEN ENDE NUSA TENGGARA TIMURFilariasis adalah penyakit menular menahun yang disebabkan oleh parasit berupa cacing filaria yang terdiri atas tiga spesies, yaitu Wucherria bancrofti, Brugaria malayi, dan Brugaria timori. Penyakit ini menginfeksi jaringan limfe (getah bening) dan menular melalui gigitan nyamuk, serta menyebabkan pembengkakan kaki, tungkai, payudara, lengan, dan organ genital. Desa Welamosa, Kabupaten Ende terletak di Provinsi Nusa Tenggara Timur (NTT) dilaporkan sebagai salah satu kecamatan dengan kasus filariasis tertinggi, yakni 40 kasus pada tahun 2015. Tujuan penelitian adalah menganalisis pengaruh faktor sosial demografi dan faktor lingkungan sosial budaya terhadap kejadian filariasis di Desa Welamosa, Kabupaten Ende. Penelitian dilaksanakan pada bulan Juli–September 2016 di Desa Welamosa dan Kecamatan Wolowaru, Kabupaten Ende. Jenis penelitian merupakan analitik observasional dan pengambilan sampel menggunakan case control sebanyak 49 orang. Instrumen penelitian menggunakan kuesioner dan ceklis. Analisis data menggunakan uji statistik program SPSS dengan backward regression logistic test. Hasil penelitian menunjukkan lima variabel yang merupakan faktor risiko kejadian filariasis, yaitu usia (OR=42,518), pendidikan (OR=38,248), pekerjaan (OR=8,404), aktivitas di luar rumah pada malam hari (OR=5,097), dan jenis kelamin (OR=0,193). Simpulan, faktor sosial demografi (usia, jenis kelamin, pekerjaan, dan pendidikan) serta faktor lingkungan sosial budaya sikap (aktivitas di luar rumah pada malam hari) merupakan faktor risiko terhadap kejadian filariasis di Desa Welamosa, Kabupaten Ende.